The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/acr.21726
|View full text |Cite
|
Sign up to set email alerts
|

Muscle mass, muscle strength, functional performance, and physical impairment in women with the hypermobility type of Ehlers‐Danlos syndrome

Abstract: Objective. To investigate lower extremity muscle mass, muscle strength, functional performance, and physical impairment in women with the Ehlers-Danlos syndrome hypermobility type (EDS-HT). Methods. Forty-three women with EDS-HT and 43 sex-and age-matched healthy control subjects participated. Muscle mass was determined by dual x-ray absorptiometry. Muscle strength and muscle strength endurance were measured with isokinetic dynamometry at angular velocities of 60, 180, and 240°/second. Static muscle endurance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 37 publications
(37 reference statements)
4
102
1
2
Order By: Relevance
“…Although a reduced sensor density has not been demonstrated in EDS-HT, the presence of muscle atrophy has indeed been shown in EDS-HT patients. [20] Therefore, the prevention of muscle atrophy by muscle training could also protect against poor proprioception. If connective tissue laxity and muscle atrophy are responsible for poor proprioception, for reasons of parsimony, this should be studied in longitudinal studies first before implementing in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a reduced sensor density has not been demonstrated in EDS-HT, the presence of muscle atrophy has indeed been shown in EDS-HT patients. [20] Therefore, the prevention of muscle atrophy by muscle training could also protect against poor proprioception. If connective tissue laxity and muscle atrophy are responsible for poor proprioception, for reasons of parsimony, this should be studied in longitudinal studies first before implementing in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…dancers) and symptomatic forms of GJH (e.g. EDS-HT, hypermobility syndrome) [19][20][21] In these studies, muscle weakness was found to be associated with pain [22] and fatigue. [21] However, whether these factors moderate the association between muscle strength and activity limitations is unknown.…”
Section: Introductionmentioning
confidence: 94%
“…Hence, it is likely that hEDS induces not only a proprioceptive deficit but, more broadly, a somatosensory deficit. Consequently, the major functional disabilities expressed by these patients, including clumsiness and falls, which sometimes lead to kinesiophobia, could be the result of this somatosensory impairment (Rombaut et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Our studies showed that EDS-HT patients have reduced knee joint proprioception [ 16 ], as well as a severely reduced quantitative muscle function and impaired in physical functioning, compared to age and sex-matched controls. EDS-HT patients present lower extremity muscle weakness, which appears not to be caused by reduced muscle mass but rather by intrinsic muscular dysfunction, associated with muscle pain and fatigue [ 17 ].…”
Section: Ehlers-danlos Syndrome Hypermobility Type (Eds-ht)mentioning
confidence: 99%